T C Conharmonic curvature tensor of Almost Kahler Manifold - Wissam Abbas Hussien; Ali. A. Shihab (Genius Journals, 2022)
This Research studied the T C Conharmonic curvature tensor of almost kahler-manifold, where this research focuses on the geometrical feature or properties of the one of the almost kahler-manifold.
Keywords: Conharmonic; tensor; almost; manifold